Advances in the study of Dientamoeba fragilis. - Chan, Francis T. H. (University of Ottawa (Canada), 1996)
Dientamoeba fragilis is a protozoan parasite first described in 1918. It resides in the human large intestine. D. fragilis has been associated with diarrhoea and abdominal pain in some patients. An indirect fluorescent antibody (IFA) assay was used to examine the presence of D. fragilis trophozoites in preserved faecal specimens. Antiserum to D. fragilis trophozoites was raised in a rabbit with a dixenic culture from the American Type Culture Collection (ATCC 30948). After absorption with Klebsiella pneumoniae and Bacteroides vulgatus, the immune rabbit serum was used for IFA examination. A total of 155 clinical samples were tested: 42 with no parasites, 9 with D. fragilis and 104 with other parasites. The IFA assay detected D. fragilis in 7/9 known positive samples. There were no false-positive IFA readings. Monoclonal antibodies (Mabs) against the parasite was produced in mice and characterized. A MAb (8B2) was obtained against an antigen released when D. fragilis was frozen and thawed. MAb 8B2 reacted with cultured D. fragilis in indirect immunofluorescence but did not react with clinical D. fragilis strains and it did not immunoblot. Another MAb (1H11) was generated against a sodium acetate-acetic acid-formalin fixed antigen. It reacted with D. fragilis isolates in patient specimens and identified a D. fragilis 39kDa protein. Susceptibility testing was performed on D. fragilis ATCC 30948. D. fragilis was cocultured with the bacteria in ATCC medium 1171. The activities of antiparasitic drugs were assessed by counting viable D. fragilis trophozoites with a haemacytometer by trypan blue exclusion. The minimal amoebicidal concentrations of the following four drugs were determined: iodoquinol at 128 $\mu$g/ml, paromomycin at 16 $\mu$g/ml, tetracycline (questionably) at 32 $\mu$g/ml, and metronidazole at 32 $\mu$g/ml. In this seroprevalence study sera from 3 symptomatic patients (F 10 y, M 12 y and F16 y), 12 age and sex-matched controls, and 189 randomly-selected healthy individuals (age range 6 months to 19 years) were tested by an indirect immunofluorescence (IIF) assay for antibodies. All 3 symptomatic patients infected with D. fragilis gave positive IIF titres of 80, and all 12 matched controls were also positive (titre ranges from 20 to 160, geometric mean titer (GMT) was 48). Of the 189 healthy children, 172 (91.0%) were positive at a serum dilution of 1 in 10, or higher. The specificity of the IIF assay was confirmed by immunoblotting 20 representative serum samples against D. fragilis (3 negative and 17 positive sera). All 17 IIF-positive serum samples identified the 39 kDa band, suggesting that this may be an important immunodominant protein of D. fragilis. (Abstract shortened by UMI.)
Keywords: Biology, Microbiology.